Prevalence of permanent childhood hearing impairment in the United Kingdom and implications for universal neonatal hearing screening: questionnaire based ascertainment study - Fortnum, Heather M (BMJ Group, 2001)
OBJECTIVE: To estimate the prevalence of confirmed permanent childhood hearing impairment and its profile across age and degree of impairment in the United Kingdom. DESIGN: Retrospective total ascertainment through sources in the health and education sectors by postal questionnaire. SETTING: Hospital based otology and audiology departments, community health clinics, education services for hearing impaired children. PARTICIPANTS: Children born from 1980 to 1995, resident in United Kingdom in 1998, with severe permanent childhood hearing impairment (hearing level in the better ear >40 dB averaged over 0.5, 1, 2, and 4 kHz). MAIN OUTCOME MEASURES: Numbers of cases with date of birth and severity of impairment converted to prevalences for each annual birth cohort (cases/1000 live births) and adjusted for underascertainment. RESULTS: 26 000 notifications ascertained 17 160 individual children. Prevalence rose from 0.91 (95% confidence interval 0.85 to 0.98) for 3 year olds to 1.65 (1.62 to 1.68) for children aged 9-16 years. Adjustment for underascertainment increased estimates to 1.07 (1.03 to 1.12) and 2.05 (2.02 to 2.08). Comparison with previous studies showed that prevalence increases with age, rather than declining with year of birth. CONCLUSIONS: Prevalence of confirmed permanent childhood hearing impairment increases until the age of 9 years to a level higher than previously estimated. Relative to current yields of universal neonatal hearing screening in the United Kingdom, which are close to 1/1000 live births, 50-90% more children are diagnosed with permanent childhood hearing impairment by the age of 9 years. Paediatric audiology services must have the capacity to achieve early identification and confirmation of these additional cases.